2019
DOI: 10.1002/cncy.22180
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HPV‐16/18 genotypes and immediate histopathologic correlation results in a Chinese population with negative cytology and positive high‐risk HPV testing

Abstract: Background The objective of this study was to examine the prevalence of human papillomavirus 16/18 (HPV‐16/18) genotypes and immediate histopathologic correlations in a Chinese population with negative cytology and positive high‐risk human papillomavirus (hrHPV) testing. Methods Patients who had documented negative cytology with immediate follow‐up (within the 6 months after negative for intraepithelial lesion or malignancy Papanicolaou [Pap] testing), including a histopathologic examination and/or hrHPV testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
2
22
2
Order By: Relevance
“…Han et al 20 found that one (1.6%) of 64 HPV‐infected patients with negative cytology had adenocarcinoma, two (3.1%) patients had adenocarcinoma in situ, and three (4.7%) patients had CIN 2/3. In a study of 1427 HPV 16‐infected women with negative cytology, Tao et al 21 demonstrated that the rate of CIN 2+ lesion was 15.2% and similar to our results. Wu et al 22 demonstrated that the risk of developing CIN 3+ lesion was significantly lower in HPV16 + other hrHPVs group compared with single HPV16 infection (OR, 0.637; 95%CI, 0.493‐0.822).…”
Section: Discussionsupporting
confidence: 91%
“…Han et al 20 found that one (1.6%) of 64 HPV‐infected patients with negative cytology had adenocarcinoma, two (3.1%) patients had adenocarcinoma in situ, and three (4.7%) patients had CIN 2/3. In a study of 1427 HPV 16‐infected women with negative cytology, Tao et al 21 demonstrated that the rate of CIN 2+ lesion was 15.2% and similar to our results. Wu et al 22 demonstrated that the risk of developing CIN 3+ lesion was significantly lower in HPV16 + other hrHPVs group compared with single HPV16 infection (OR, 0.637; 95%CI, 0.493‐0.822).…”
Section: Discussionsupporting
confidence: 91%
“…These results are essentially in agreement with studies from Western countries and the benchmark ranges from the 2010 CAP survey in the United States 2 . In our previous studies, we observed that the CPT had performance comparable to that of liquid‐based cytology for predicting CIN2+ lesions in Chinese women who had negative cytology or low‐grade squamous intraepithelial lesion cytology 10,11 . The current study demonstrated that, although the CPT preparation method had the lowest reporting rate among the 3 methods, the performance of the CPT method for predicting CIN was comparable to the performance of the ThinPrep and SurePath methods (35.5% vs 35.9% and 32.1%, respectively).…”
Section: Discussionsupporting
confidence: 89%
“…We previously published a series of investigations on the reporting rates, HPV testing results, and immediate histologic follow‐up data in Chinese women with different cytology diagnosis categories, including negative cytology, low‐grade squamous intraepithelial lesion, and high‐grade squamous intraepithelial lesion at OGHFU 9‐11 . Herein, we report our experience with ASC‐US cytology, the most common cytologic abnormality in cervical Pap tests, to provide baseline information for establishing the appropriate clinical management of cervical cancer screening for the Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Han et al 22 33 In another retrospective study, the results from the Cobas assay demonstrated a slightly lower HPV-16 and/or HPV-18 prevalence in Chinese women with NILM/hrHPV+ (17.6% for HPV-16, 6.2% for HPV-18, and 0.6% for HPV-16 and HPV-18) than in Korean women. 34 The distribution of HPV genotypes in women with NILM/hrHPV+ differs among countries; this may be attributed to different subtypes of HPV infection in different races and regions, and the different detection platforms. 35 As mentioned earlier, the mRNA-based AHPV assay has been found to be more specific in detecting high-grade cervical lesions.…”
Section: Discussionmentioning
confidence: 99%